Metabolic state of the bone tissue in patients with false joints of long bones against a background of hyperhomocysteinaemia and associated disturbances - Bezsmertniy, Yuriy (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2013)
The purpose of the present research was to study the metabolic state and mineral density of the bone tissue in patients with false joints of long bones and assess their relations with levels of homocysteine, total cholesterol and interleukin 6. Values of mineral density of the bone tissue and levels of homocysteine (HC), total cholesterol (TCS), interleukin 6, transforming growth factor beta 1 (TGF-β1), osteocalcin, cartilage oligomeric matrix protein (COMC), C-terminal propeptide of collagen type I (CICP) and pyridinoline cross-links were examined in 153 patients with false joints of long bones. It was found out that higher levels of HC, TCS and interleukin 6 in blood serum produced a detrimental effect of the structural-functional state of the bone tissue and was accompanied with increased amounts of pyridinoline and COMP, lower levels of osteocalcin, CICP and TGF-β1, as well as mineral density values of the bone tissue. It was proved that increases in blood serum levels of HC, TCS and interleukin 6 were negative determinants for the metabolic state of the bone tissue and associated with inhibition of biosynthetic processes and intensification of destructive ones, as well as with systemic and local loss of the mineral density of the bone tissue. Aberrant levels of HC, TCS and interleukin 6 were predictors of a disturbance in the structural-functional state of the bone tissue in patients with false joints of long bones.